Plastic limit analysis of plates, shells, and disks - Save, M. A. (North-Holland series in applied mathematics and mechanics, 1997)
This revised and updated edition of a book first published in 1972 has kept the general features of the first edition but as could be expected after two decades there are also substantial differences. For instance optimal design has been completely deleted as the developments in this field have been so great that it warrants a book in itself. The fundamental concepts based on Drucker's postulate rather than those of Prager's assumptions function have been introduced. Problems of cyclic loading have been given some more extensive treatment, both in the general theory and in applications. General indications and references have been added for reinforced concrete plates and shells. A general presentation of the yield condition for both plates and shells has been included and the section on the influence of axial force in plates has been almost re-written. Finally, a chapter has been added exclusively devoted to the numerical approach to limit load and shake-down load evaluation. Like the previous edition the book is directed towards engineering applications. The theory is rigorously developed and is therefore of great use to engineering students in plastic limit analysis. Furthermore, applications to metal and reinforced concrete plates and shells and to metal disks are treated by both analytical and numerical approaches.